TINJAUAN PERHITUNGAN, PEMOTONGAN, PELAPORAN PPH 21 ATAS BUKAN PEGAWAI MENERIMA IMBALAN BERKESINAMBUNGAN PADA KOPERASI SOS OLEH KAP HSR&R - Sekar Oktaviola Sendin (2023)
The SOS Cooperative is a BUMN cooperative engaged in telecommunication services and repairs. The SOS Cooperative also has employees who of course receive rewards in the form of salaries. Not only have employees, but Cooperatives have supervisors and administrators who get rewards that are sustainable. The SOS Cooperative also performs its own calculations for several matters such as Income Tax Article 21. In calculating Income Tax Article 21, the SOS Cooperative is wrong in calculating the tax payable in 2021 which causes large prepaid tax costs to arise. So doing the writing of this final project to find out the calculations. Withholding and reporting of income tax article 21 in 2022. This writing uses a descriptive method by describing the final results in the form of data that has been obtained using several methods such as observation, interviews and documentation. This writing shows that the tally calculations for 2022 are in accordance with the applicable provisions. But in reporting in the form of a notification letter (SPT) there is a late report so that late reporting fines arise.